Effects of tree planting geometry on lentil nutritional quality, tree biomass, and economic returns in Melia dubia-based agroforestry system in Bundelkhand region of India - Deshmukh, Pradyumna Prataprao; Tiwari, Prabhat; Dobriyal, Manmohan J.; Yadav, Ram Prakash; Handa, A. K.; Kumar, Naresh; Ram, Asha; Dev, Inder; Yadav, Ashok; Anuragi, Hirdayesh; Shukla, A. K.; Shekhawat, Varsha; et al. (Frontiers in Agronomy, 2025)
IntroductionLow farm productivity, declining soil fertility, and climatic stress in the semi-arid Bundelkhand region demand sustainable land-use strategies. Integrating Melia dubia with lentil-based systems offers potential to enhance soil fertility, resource efficiency, and profitability. However, limited studies have examined how tree spacing influences lentil seed quality, litterfall nutrient dynamics, and carbon sequestration in M. dubia-based agroforestry.MethodsA field experiment was conducted during the 2023–24 Rabi season at the Forestry Research Farm, Rani Lakshmi Bai Central Agricultural University, Jhansi, India. The study employed a split-plot design with three M. dubia spacings (5 × 5 m, 5 × 4 m, and 5 × 3 m) and two lentil varieties (IPL 316 and L 4727), along with a sole crop control, replicated thrice. Observations included lentil nutrient composition, litterfall quantity and nutrient content, tree growth, biomass, carbon storage, and economic returns. Statistical analysis was performed using OPSTAT software.ResultsTree spacing significantly affected lentil nutrient composition, litterfall production, and system productivity. The 5 × 4 m spacing recorded the highest lentil seed protein (26.21%) and nitrogen (4.19%) contents, whereas phosphorus and calcium were maximum under 5 × 3 m spacing (0.45% and 0.58%, respectively). Variety IPL 316 exhibited superior nutrient profiles with higher nitrogen, potassium, calcium, copper, and zinc concentrations compared to L 4727. Denser plantations (5 × 3 m) produced maximum litterfall (1.19 Mg ha⁻¹), with peak nutrient release during January–February, indicating efficient nutrient recycling. Phosphorus and potassium concentrations in litter were also higher under closer spacings. Photosynthetically active radiation (PAR) decreased with increasing tree density, ranging from 652.85 µmol m⁻² s⁻¹ in sole lentil to 135.26 µmol m⁻² s⁻¹ under 5 × 3 m spacing. The 5 × 3 m spacing achieved the highest total biomass (42.7 Mg ha⁻¹), carbon stock (21.32 Mg ha⁻¹), and CO₂ sequestration potential (78.37 Mg ha⁻¹). Economically, the same spacing yielded maximum gross returns (US$ 4227 ha⁻¹), net returns (US$ 2783 ha⁻¹), and benefit–cost ratio (2.92).ConclusionIn conclusion, closer planting geometry of M. dubia (5 × 3 m) enhanced biomass, carbon storage, and profitability without compromising lentil quality. The integration of lentil under M. dubia optimized resource use, nutrient cycling, and carbon sequestration, demonstrating its suitability for sustainable and climate-resilient agroforestry in Bundelkhand.